Appearances Can Be Deceiving: A Case Report of Asymptomatic Appendiceal Goblet Cell Adenocarcinoma Presenting as an Ovarian Tumor - Hiroko Fukasawa; Rei Gou; Kota Tanaka; Yuri Tada; Hikaru Tagaya; Shinji Furuya; Naoki Oishi; Akihiko Hashi; Osamu Yoshino (Case Reports in Oncology)
Introduction: Goblet cell adenocarcinoma (GCA) of the appendix is an uncommon type of cancer that includes both epithelial and neuroendocrine features, with goblet cells present. These tumors have traditionally been viewed as one of the more aggressive forms of appendiceal cancer, frequently being diagnosed at a metastatic stage. For patients with stage III–IV disease, the 5-year overall survival rate ranges from 14% to 22%. Due to limited data, the diagnosis and management of GCA are challenging. Case Presentation: We present the case of a 55-year-old female who presented with elevated serum carcinoembryonic antigen levels and a left ovarian tumor. Preoperative imaging indicated a normal appendix. During surgery for suspected ovarian carcinoma, frozen section analysis revealed mucinous adenocarcinoma of the ovary, but distinguishing between primary and metastatic lesions was challenging. Meticulous exploration revealed a firm and thickened appendix, prompting appendectomy and subsequent diagnosis of appendiceal GCA with ovarian metastasis. Conclusion: Pathologies of the appendix, like GCA, can mimic ovarian tumors despite a normal-looking appendix, complicating diagnosis. Through this case, we underscored the need for careful intraoperative examination of the appendix in patients with mucinous ovarian neoplasms to avoid misdiagnosis and ensure appropriate treatment.